ANALISIS STRUKTUR, PERILAKU DAN KINERJA INDUSTRI MINUMAN DI INDONESIA PERIODE 2006 – 2009 - Biondi Mahesa (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2010)
This study purpose is to analyze the structure, behavior and performance of the Beverage Industry in Indonesia, concentration ratio and Nerfindahl index are used to see market structure of Beverage Industri condust their activity. Descriptive analysis is used to analyze the market behavior of firms in the beverage industry.The data used in this research is secondary data, and period of research is from2006 until 2009. These studies show that market structure of Softdrink Industry in Indonesia is tight oligopoly the average concentration ratio of the four largest firms (CR4) is 97.83 percent and thebehavior of firms in determining prices is influenced by the rival pricing. Themarket beverage industry in Indonesia tends to become less competitive orconcentrated, so need oversight by the government to supervise the business activities which indicated a dominant position is and too difficult for new entrants beverage industry market in Indonesia.Keywords : PDB, CRn, IHH, Market Structure Oligopoly